Pengaruh Tunjangan Pegawai terhadap Kinerja Pegawai pada Kantor Dewan Perwakilan Rakyat Daerah (DPRD) Kabupaten Mamasa - Ermiaty Febrini Elviona Pualillin; Zainal Ruma; Burhanuddin Burhanuddin; M. Ikhwan Maulana Haeruddin; Uhud Darmawan Natsir (Fakultas Ekonomi & Bisnis, Univ, 2026)
This study was designed to measure the extent to which employee benefits influence employee performance within the Regional House of Representatives of Mamasa Regency office environment. The research employed an associative quantitative approach and involved all 51 employees as research subjects using a saturated sampling technique. Data were collected through questionnaires, direct observation, and document analysis, then processed using multiple regression analysis assisted by SPSS version 25. The findings revealed that employee salaries and benefits have a positive and significant effect on employee performance, with a significance value of 0.017 < 0.05. The regression analysis also showed that both variables provide a significant influence on employee performance, indicated by an F-count value of 67.260, which is greater than the F-table value of 3.19. In addition, the coefficient of determination value of 0.784 indicates that 78.4% of the variation in employee performance can be explained by employee income and benefits. These findings demonstrate that adequate employee compensation is a crucial factor in encouraging higher motivation, improving work productivity, and supporting better employee performance within the organization.